The principles of recovery-oriented mental health services: A review of the guidelines from five different countries for developing a protocol to be implemented in Yogyakarta, Indonesia. - M A Subandi; Maryama Nihayah; Carla R Marchira; Trihayuning Tyas; Ariana Marastuti; Ratri Pratiwi; Fiddina Mediola; Yohanes K Herdiyanto; Osi Kusuma Sari; Mary-Jo D Good; Byron J Good (PLoS ONE, 2023)
Background Recovery-oriented mental health service has become the focus of global change in mental health services. Most of North industrialized countries have adopted and implemented this paradigm in the last two decades. Only recently that some developing countries are trying to follow this step. In Indonesia's case, there has been little attention to developing a recovery orientation by mental health authorities. The aim of this article is to synthesize and analyze the recovery-oriented guidelines from five industrialized countries that we can use as a primary model for developing a protocol to be implemented in community health centre in Kulonprogo District, Yogyakarta, Indonesia. Method We used a narrative literature review by searching for guidelines from many different sources. We found 57 guidelines, but only 13 from five countries met the criteria, including five guidelines from Australia, one from Ireland, three from Canada, two from the UK, and two from the US. To analyze the data, we used an inductive thematic analysis to explore the themes of each principle as described by the guideline. Result The results of the thematic analysis revealed seven recovery principles, including (1) cultivating positive hope, (2) establishing partnerships and collaboration, (3) ensuring organizational commitment and evaluation, (4) recognizing the consumer's rights, (5) focusing on person-centeredness and empowerment, (6) recognizing an individual's uniqueness and social context, and (7) facilitating social support,. These seven principles are not independent, rather they are interrelated and overlap each other. Conclusion The principle of person-centeredness and empowerment is central to the recovery-oriented mental health system, while the principle of hope is also essential to embracing all the other principles. We will adjust and implement the result of the review in our project focusing on developing recovery-oriented mental health service in the community health center in Yogyakarta, Indonesia. We hope that this framework will be adopted by the central government in Indonesia and other developing countries.